Percutaneous carotid artery access in infants < 3 months of age. Issue 4 (23rd December 2015) - Choudhry, Swati; Balzer, David; Murphy, Joshua; Nicolas, Ramzi; Shahanavaz, Shabana
Abstract : Background: Carotid artery access in infants with congenital heart disease undergoing cardiac catheterization via a surgical cut down has been well described. There is a paucity of information regarding percutaneous carotid artery (CA) access in infants <3 months. Methods: A retrospective review of infants <3 months of age undergoing cardiac catheterization via percutaneous CA approach was performed after IRB approval. Between January 2012 and May 2015, 18 patients underwent 20 procedures; median age 13 days (2–77); median weight 3.3 kg (1.6–5). Procedures performed were patent ductus arteriosus (PDA) stenting (8), modified blalock taussig (BT) shunt stenting (3), balloon aortic valvuloplasty (6), and balloon angioplasty of coarctation (3). Results: Percutaneous access was obtained with a Doppler needle under ultrasound guidance into the right (16) and left CA (4). Sheath size used was 4 Fr (17), 5 Fr (2), and 6 Fr (1). Median time to sheath insertion was 6.5 min (2–20). Percutaneous access was obtained successfully in all cases. There were no major procedural complications. There were two minor complications; hypotension, and ductal spasm. Hemostasis was achieved by manual compression; median time was 14.5 min (8–36). There were two post‐procedural complications involving development of CA pseudo aneurysms that were repaired surgically. Post‐procedure CA patency was documented by angiography (3), MRA (3), or vascular ultrasound (14). There were no documented arterial occlusions. Conclusion: Our experience suggests that percutaneous CA access in infants <3 months of age is safe and feasible with preserved vascular patency and no neurological adverse events. © 2015 Wiley Periodicals, Inc.